2018
DOI: 10.1002/hep.30151
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Improves Prediction of Short‐Term Mortality in Critically Ill Patients With Cirrhosis: A Multinational Study

Abstract: Lactate levels reflect appropriately severity of disease and organ failure and were independently associated with short-term mortality in critically ill patients with liver cirrhosis. Lactate is a simple but accurate prognostic marker and its incorporation improved performance of CLIF-C ACLFs significantly. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(138 citation statements)
references
References 48 publications
5
129
1
3
Order By: Relevance
“…Management of liver injury in critical illness represents a major multidisciplinary challenge. Liver injury in critical illness may be divided into groups: On the one hand, liver cirrhosis and subsequent acute‐on‐chronic liver failure (ACLF) and primary acute liver failure (ALF) are well‐known entities of primary hepatic dysfunction . However, secondary or acquired liver injury and failure (primarily without underlying liver disease) such as hypoxic liver injury (HLI), cholestatic dysfunction in critical illness, sclerosing cholangitis in critical illness (SC‐CIP), and drug‐induced liver injury (DILI) represent by far the most frequent forms of hepatic injury in critical illness.…”
Section: Prevalence and Outcome Of Different Liver Disease Entities Amentioning
confidence: 99%
See 1 more Smart Citation
“…Management of liver injury in critical illness represents a major multidisciplinary challenge. Liver injury in critical illness may be divided into groups: On the one hand, liver cirrhosis and subsequent acute‐on‐chronic liver failure (ACLF) and primary acute liver failure (ALF) are well‐known entities of primary hepatic dysfunction . However, secondary or acquired liver injury and failure (primarily without underlying liver disease) such as hypoxic liver injury (HLI), cholestatic dysfunction in critical illness, sclerosing cholangitis in critical illness (SC‐CIP), and drug‐induced liver injury (DILI) represent by far the most frequent forms of hepatic injury in critical illness.…”
Section: Prevalence and Outcome Of Different Liver Disease Entities Amentioning
confidence: 99%
“…Liver injury in critical illness may be divided into groups: On the one hand, liver cirrhosis and subsequent acute-on-chronic liver failure (ACLF) and primary acute liver failure (ALF) are well-known entities of primary hepatic dysfunction. (4)(5)(6)(7)(8) However, secondary or acquired liver injury and failure (primarily without underlying liver disease) such as hypoxic liver injury (HLI), cholestatic dysfunction in critical illness, sclerosing cholangitis in critical illness (SC-CIP), and drug-induced liver injury (DILI) represent by far the most frequent forms of hepatic injury in critical illness. Although liver failure in the absence of chronic liver diseases refers primarily to the unique entity of ALF, defined as onset of hepatic encephalopathy and hepatic coagulopathy in patients without underlying liver disease (despite some exceptions), secondary forms of liver injury can also fulfill diagnostic criteria of ALF and are consequently incorporated into the recent European guidelines on ALF.…”
Section: Liver Injury and Failure In Critical Illnessmentioning
confidence: 99%
“…Lactate levels were independently associated with short-term mortality in critically ill patients with liver cirrhosis and were shown to significantly improve performance of CLIF-C ACLF. The modified called CLIF-C ACLFsLact score remains to be evaluated in an external cohort 41 together with the numerous biomarkers that have recently been associated with outcomes in this population. [42][43][44][45][46][47] Combining available scores with biomarkers could optimize prediction of events in this population with a high short-term mortality.…”
Section: Key Pointsmentioning
confidence: 99%
“…On the one hand, hyperglycemia is always associated with hyperlactatemia [9,10], increasing morbidity and mortality in acute critical illness [11,12]. A previous confirmed that lactate levels might appropriately reflect the severity of disease and organ failure, and also were independently associated with short-term mortality in critically ill patients with liver cirrhosis [13]. Although anaerobic glycolysis increases the substrate, however, suppressing hyperglycemia generating 2,3diphosphoglycerate, absolute insulin secretion, or relatively insufficient may lead to an increase in plasma free fatty acid concentration, and fatty acid can increase the myocardial oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%